Data from: A landscape of coexistence for a large predator in a human dominated landscape - Gehr, Benedikt; Hofer, Elizabeth J.; Muff, Stefanie; Ryser, Andreas; Vimercati, Eric; Vogt, Kristina; Keller, Lukas F. (Zenodo, 2020)
Human related mortality is a major threat for large carnivores all over the world and there is increasing evidence that large predators respond to human related risks in a similar way as prey respond to predation risk. This insight recently led to the conceptual development of a landscape of coexistence that can be used to identify areas which can sustain large predator populations in human dominated landscapes. In this study we applied the landscape of coexistence concept to a large predator in Europe. We investigated to what extent Eurasian lynx ( Lynx lynx ) habitat selection is affected by human disturbance in a human dominated landscape. More specifically, we were interested in the existence of a tradeoff between the availability of roe deer, one of their main prey and avoidance of human disturbance and how this affects the spatio-temporal space use patterns of lynx. We found that lynx face a tradeoff between high prey availability and avoidance of human disturbance and that they respond to this by using areas of high prey availability (but also high human disturbance) during the night when human activity is low. Furthermore our analysis showed that lynx increase their travelling speed and remain more in cover when they are close to areas of high human disturbance. Despite clear behavioral adjustments in response to human presence, prey availability still proved to be the most important predictor of lynx occurrence at small spatial scale, whereas human disturbance was considerably less important. The results of our study demonstrate how spatio-temporal adaptations in habitat selection enable large carnivores to persist in human dominated landscapes and demonstrate the usefulness of the concept of a landscape of coexistence to develop adaptive management plans for endangered populations of large carnivores. deer_data This table contains the GPS locations of roe deer associated with habitat variables and temporal variables that were used to build a habitat model (RSF) for roe deer. The table is divided into ...